PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL INTERAKTIF KALKULUS-II DALAM PENINGKATAN PRESTASI BELAJAR MAHASISWA - Mustafidah, Hindayati (UMP, 2010)
This research is based of students low learning achievement of students in calculus II courses coupled with a lack of students learning activities. Accordingly, in this study developed a system of interactive CD containing the course material of Integral in Calculus II subject, to assist students in learning the course material. The method used is developing with the following specifications: the model used in this development is the creation of interactive multimedia learning CD that contains material of Integral, practice items and their solutions, the manual of this media. Design validation is performed by experts (lecturer of this course) and validation of users (students) as a field test. Technique data collecting by observation, interviews, and tests. Research instruments include instructional media that consists of instructional materials, computer hardware and software that supported. Evaluation tools are used are test and observation sheets. Technique of data analysis using descriptive statistical analysis of quantitative in the form of average. This research result is a system of interactive multimedia CD that contains material that covers Integral Calculus and Its Application. The effectiveness of this system has been tested by the increasing activities of students learning and increase student achievement of an integral material that is reflected by scores that tend to increase.Keywords: interactive learning media, Integral, student achievement